THE TEACHING SPEAKING IN TC GRADE AT HAPPY ENGLISH COURSE 2 PARE KEDIRI - anifah, zumrotul (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The aims of this research is to describe (1) the students’ background, (2) the tutor’s background, (3) thethe teaching of speaking at Happy English Course 2 in the terms of curriculum, syllabus, lesson plan, materials, media, the technique and the evaluation, (4) the implementation of teaching speaking in TC grade in the term of pre-teaching, whilst teaching, and post-teaching, (5) the students’ respon in teaching speaking at Happy English Course 2, (6) students’ achievement  in speaking English at Happy English Course 2. The methodology used in this case was descriptive qualitative research. the subject of this study was the director, the tutor and the students at TC grade. The data collection methods were observation, interview, questionnaire, and documentation. Therefore, the data was displayed, reduced and verified based on the result of the research. From the result, it can be concluded that (1) the students’ background is bad related to the level and age but related to the skill of the English is very good, (2)tutor’s background is enough, (3) the teaching speaking at Happy English Course in the terms of (a) curricullum is enough, (b) the syllabus is good, (c) lesson plan is bad, (d) the materiaal is good, (e) the technique is good, (f) the media is good, (g) the evaluation is enough (4) the implementation of teaching speaking in the terms of (a) pre teaching is very good,(b) whilst teaching is good(c) post teaching was enough.(5) the students’ respond is good(6) the students’ achievement in speaking English is very good.